Optimized-Unet: Novel Algorithm for Parapapillary Atrophy Segmentation - Wan, Cheng; Wu, Jiasheng; Li, Han; Yan, Zhipeng; Wang, Chenghu; Jiang, Qin; Cao, Guofan; Xu, Yanwu; Yang, Weihua (Frontiers in Neuroscience, 2021)
In recent years, an increasing number of people have myopia in China, especially the younger generation. Common myopia may develop into high myopia. High myopia causes visual impairment and blindness. Parapapillary atrophy (PPA) is a typical retinal pathology related to high myopia, which is also a basic clue for diagnosing high myopia. Therefore, accurate segmentation of the PPA is essential for high myopia diagnosis and treatment. In this study, we propose an optimized Unet (OT-Unet) to solve this important task. OT-Unet uses one of the pre-trained models :Visual Geometry Group(VGG), ResNet, and Res2Net, as a backbone and is combined with edge attention, parallel partial decoder, and reverse attention modules to improve the segmentation accuracy. In general, using the pre-trained models can improve the accuracy with fewer samples. The edge attention module extracts contour information, the parallel partial decoder module combines the multi-scale features, and the reverse attention module integrates high- and low-level features. We also propose an augmented loss function to increase the weight of complex pixels to enable the network to segment more complex lesion areas. Based on a public dataset (PALM), the proposed OT-Unet achieves a high accuracy of 0.9922, indicating a significant improvement over the original Unet (0.9769).